Influences of the tank liquid lateral sloshing and mass time-varying on high clearance self-propelled sprayer ride comfort - Lu, Liquan; Zhang, Junchang; Cui, Cui; Chen, Jun; Chen, Yu; Jing, Hongling; Zhang, Shuo; Adilet, Sugirbay; Hu, Chenwei; Cao, Jiayu (International Journal of Agricultural and Biological Engineering, 2024)
To explore the influence of the lateral sloshing and the time-varying mass of the liquid in the tank on the ride comfort of the high-clearance sprayer, a spring-mass-damping equivalent mechanics that can describe the lateral sloshing of the liquid under different filling ratios was constructed based on the equivalent criterion. The Fluent was used to simulate the moment acting on the wall of the tank by the lateral sloshing of the liquid, and then the parameters of the equivalent mechanical model are obtained by fitting and solving. Comparative analysis of Fluent simulation and bench test on lateral sloshing of tank liquid under different filling ratios. The results show that the lateral sloshing trend of the tank liquid level obtained from the Fluent simulation and the bench test was consistent, which proved the accuracy of the Fluent fluid simulation process and the correctness of the required equivalent mechanical model parameters. Incorporating a liquid sloshing equivalent model, a four-degree-of-freedom vertical dynamic model of the sprayer half-car was established. Subsequently, the performance of the sprayer was systematically analyzed and compared under the excitation of a bump road and a random E-level road. This investigation took into account varying liquid filling ratios of 10%, 50%, and 90%. The focus lay on evaluating the vertical acceleration of the sprayer body, dynamic deflection of the suspension, and dynamic load on the tires in response to these road conditions. This analysis is conducted independently of the liquid sloshing factor. The results show that the lateral sloshing of the liquid medicine significantly reduces the ride smoothness of the machine, and makes the vibration response of the machine produce a certain hysteresis effect. With the reduction of the quality of the liquid medicine in the spray tank, the vibration amplitude of the sprayer body gradually decreases, the hysteresis effect is also gradually weakened. The results presented in this study offer a theoretical foundation for the analysis of ride comfort and the optimization of chassis structure in high-clearance sprayers. Keywords: high clearance self-propelled sprayer, liquid lateral sloshing, ride comfort, system dynamics, simulation DOI: 10.25165/j.ijabe.20241701.7798 Citation: Lu L Q, Zhang J C, Cui C, Chen J, Chen Y, Jing H L, et al. Influences of the tank liquid lateral sloshing and mass time-varying on high clearance self-propelled sprayer ride comfort. Int J Agric & Biol Eng, 2024; 17(1): 12-22.